Developing STEM-Based Interactive Learning Modules Integrating Samawa Local Culture to Enhance Students’ Conceptual Understanding and Science Process Skills - Ardianti, Suji; Yahya, Fahmi; Fatmawati, Fatmawati; Anggraeni, Wulan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study developed and tested the effectiveness of an interactive learning module based on Science, Technology, Engineering, and Mathematics (STEM) integrated with the local culture of Samawa. The main objective was to improve students' conceptual understanding and science process skills of SMA Negeri 4 Sumbawa Besar on kinematics material. Using the ADDIE model research and development (R&D) method, the module was validated by material and media experts before being tested on 30 students through a One-Group Pretest-Posttest design. The validation results showed that the module was very feasible to use, while the implementation test results showed a significant increase in conceptual understanding (N-Gain = 0.65) and science process skills (N-Gain = 0.75). Thus, this module is proven to be effective as an alternative teaching material that is contextual and relevant to the demands of 21st-century learning.